Pengaruh Citra Merek, Kepercayaan Merek, Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Fiesta Chicken Nugget Di Kota Tasikmalaya - Mukarom, Muhammad Rifki Danil; Pauzy, Depy Muhamad; Karmila, Mila (Universitas Dehasen Bengkulu, 2024)
This research aims to determine the influence of brand image, brand trust, and product quality on purchasing decision of Fiesta Chicken Nugget products among consumers at Tasikmalaya . The method used is quantitative with a research sample of 100 respondents. The data used are primary and secondary data. The analytical tool used in this research is multiple linear regression analysis using SPSS version 29. Based on the results of this research, it shows that brand image, brand trust and product quality simultaneously have a positive and significant effect on purchasing decision. Brand image partially has a significant effect on purchasing decision. Brand trust partially has a significant effect on purchasing decision. Product quality partially has a significant effect on purchasing decision.